05 PERSEPSI KONSUMEN TERHADAP PRODUK GULA SORGUM (Studi Kasus : di Kecamatan Lau, Kabupaten Maros) - Jurnal Agribis; Syamsul Syamsul; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
Public consumption of sugar and other sweeteners as daily basic needs is increasing every year, along with the increasing population. The sugar-rich stalk of sweet sorghum has great potential for sugar, syrup, and as a sweetener. The characteristics of sweet sorghum stalks can produce sap similar to those produced by sugar cane. This study aims to determine consumer perceptions of sorghum sugar products and what factors influence consumer perceptions of sorghum sugar products. This type of research is a quantitative descriptive study with a survey approach. The research location is in Lau District, Maros Regency. The research sample was consumers of sorghum sugar who were selected by accidental sampling method with a total of 30 consumer respondents. Data collection techniques using questionnaires and documentation. To analyze consumer perceptions of sorghum sugar, index analysis techniques were used and multiple regression analysis models were used to analyze the factors affecting consumer perceptions of sorghum sugar. The results showed that: (1) Consumer perceptions of sorghum sugar products in Lau District, Maros Regency were included in the medium category with a value of 63.11%, and (2) The factors that significantly influence consumer perceptions of sorghum sugar products are taste, aroma, and texture.